Fuzzy ARTMAP with binary relevance for multi-label classification - Yuan, L.X. (Springer Science and Business Media Deutschland GmbH, 2018)
In this paper, we propose a modified supervised adaptive resonance theory neural network, namely Fuzzy ARTMAP (FAM), to undertake multi-label data classification tasks. FAM is integrated with the binary relevance (BR) technique to form BR-FAM. The effectiveness of BR-FAM is evaluated using two benchmark multi-label data classification problems. Its results are compared with those other methods in the literature. The performance of BR-FAM is encouraging, which indicate the potential of FAM-based models for handling multi-label data classification tasks. Â© Springer International Publishing AG 2018.